(untitled) (Research, Society and Development, 2022)
Water resources are of great importance in the maintenance of human life and health, and their quality can deteriorate as irregular occupations progress, which can contaminate groundwater resources. In Brazil, the Ministry of Health has ordinances that set parameters for the potability of groundwater for human consumption. The objective of this work is to evaluate the quality of water from wells in the Vista Alegre do Juá Occupation in the municipality of Santarém, through Ordinance 888/21 of the Ministry of Health and 396/08 Conama. The samples were collected in three tubular-type wells, to evaluate 12 physical-chemical parameters, comparing the results with standards pre-established by current legislation. The three analyzed wells presented three of the 12 analyzed parameters analyzed outside the allowed limits by the legislation, namely: phosphorus, nitrate, and turbidity, except for, well, three for this last parameter. These changes are mainly related to the decomposition of tree roots from recent deforestation and the natural flow of rain that carries nutrients from higher to lower areas where the wells are located. The mentioned parameters make water unsuitable for consumption without treatment and have effects on its palatability, conferring laxative properties and other health risks if consumed for long periods without proper treatment. Thus, this study highlights the need to evaluate more wells and support residents on the use of water disinfection methods before consumption to avoid waterborne diseases.